Videotron sebagai Media Informasi Humas Pemerintahan Kabupaten Sidoarjo - Ruddy Purnama; Didik Hariyanto (Kanal: Jurnal Ilmu Komunikasi, 2017)
The purpose of this research is to describe the function of videotron as information media of Sidoarjo local government’s public relations. The method used in this research is descriptive qualitative. Informants in this study is Sidoarjo local government’s public relations and five people of users Jl A Yani Sidoarjo. Data collection techniques used in this study are in-depth interviews (indepth interview), observation, and documentation. Data analysis developed by Miles and Hubberman includes data reduction, data presentation and conclusions. The results of this study indicate that the videotron function that is managed by Sidoarjo local government’s public relations is considered quite effective in assisting the performance and Sidoarjo local government’s public relations role as a communicator to convey all important information related to administration of Sidoarjo Local Government.